Prospects of anti-B-cell therapy for systemic sclerosis - E. L. Nasonov; L. P. Ananyeva (Научно-практическая ревматология, 2025)
Systemic sclerosis (SSc) is a severe systemic autoimmune rheumatic disease (SARD), pathogenetically associated with inflammation and pathological disorders in the microvascular bed, leading to the development of autoimmune fibrosis and vasculopathy. An important role in the pathogenesis of SSc is played by pathological activation of B-cell immunity, manifested in the disruption of B-cell signaling, B-cell homeostasis, hyperproduction of “profibrotic” cytokines and “pathogenic” autoantibodies. Despite the fact that the pathogenetic mechanisms of SSc associated with dysregulation of B cells and the synthesis of “sclerodermic” autoantibodies have not been sufficiently studied, anti-B-cell therapy is considered one of the important areas of treatment for this disease. The article examines modern concepts about the place of anti-B-cell therapy in the treatment of SSc, primarily in relation to the progression of interstitial lung diseases and skin lesions, and discusses the results of the use of new types of monoclonal antibodies to B-cells and CAR-T-cell therapy.